Human SLC11A1 gene polymorphism has the propensity to confer susceptibility to M. africanum TB disease in Gh - Asante-Poku, Adwoa; Morgan, Portia; Aboagye, Samuel Yaw (Preprints, 2020)
Human tuberculosis (TB) is caused mainly by Mycobacterium tuberculosis (MTB) and M. africanum (MAF) remains a major global health threat. The varying response of different host to contact with the TB bacteria, indicates the importance of host genetics in susceptibility to TB disease. We explored the association among selected human/host genomic variants and disease caused by the two causative pathogens in Ghana through a case control study. MTBC isolates (323) recovered from pulmonary TB patients recruited between 2016 and 2018 were genotyped using spoligotyping. A selection of 29 SNPs from MTB-related genes with high frequency among African populations were genotyped using a TaqMan® SNP Genotyping Assay and iPLEX Gold Sequenom Mass Genotyping Array. Associations between MTBC lineages and host variables were assessed using univariate and multivariate logistic regression. The prevalence of MTB and Maf among the participants were 79% and 21% respectively. Association analysis between the controls and MAF showed that rs2695342 variant on the SIC11A1 gene have the propensity to confer susceptibility to MAF infections (P = 0.093, OR = 8.35, 95% CI = 0.70 – 99.24) whilst the rs17048476 (P = 0.088, OR = 1.57, 95% CI = 0.93 – 2.63) and rs1482868 (P = 0.095, OR = 0.60, 95% CI = 0.33 – 1.09) were observed to be only suggestive. Our findings implicate SLC11A1 as a potential susceptibility gene of substantial interest for TB caused by MAF which is an important pathogen in West Africa and highlight the need for in-depth host pathogen studies in West Africa.
Keywords: Tuberculosis; Host pathogen interactions; SNPs; University of Ghana; WACCBIP_NCDS; ACE: Cell Biology of Infectious and Non-Communicable Diseases; Prince Asare; Isaac Darko Otchere